Multikulturalisme dalam Karya Ulama Nusantara - Abdul Khobir; Muhamad Jaeni; Abdul Basith (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2019)
This study discusses form and dimensions of a text regarding multiculturalism concept in the ulama books of the 20th century, how the text was produced and consumed by the community, and the sociocultural praxis contained in it. The collected data were analyzed by using descriptive method and content analysis. The results of this study show that multiculturalism discourses written by Indonesian Ulama include: appreciation of Javanese language locality, gender equality, respect for the diversity of local economic potentials, the importance of national unity and counter to the negative stigma of Indonesian archipelago. At the level of text, multiculturalism discourses are written in the form of nadham and natsar (prose), and the language variety ​​used is Arabic pegon script. In the case of social praxis, multicultural values ​​are divided into two, namely social and religious discourse. The social discourse discusses social problems, equality, the importance of respecting differences as well as loving the motherland, while the religious discourse describes some problems developed in the society. In this case, the religious proposition is used as a basis for strengthening as well as elaborating the muticulturalism values.